POLISI, KEKERASAN DAN SENJATA API - Irsan, Koesparmono; Putri, Anggreany Haryani (KRTHA BHAYANGKARA, 2018)
Brimob is a special top of Indonesian National Police Force, Brimob was trained to face special crimes using guns and other special weapon to face crimes using force. All politics is a struggle for power is violence. The reemergence in the early 1980s of terrorism motivated by a religions imperative and state-sponsored terrorist set in motion perfound changes in the nature, motivations and capabilitis of terrorist that are still unfolding. Torture is used as a strategic component of state security system to achieve board political ends thorugh the victimizaztion of individuals which serves pain of suffering, wether physical of metal, is intentionally inflicted : ‘many person, of course, harbor all sorts of radical and extreme belifts and opinion, and many of them belong to radical or even illegal of proscribed political organization. However, if they do not use violence in the pursuance of their beliefs, they cannot be considered terrorist. The willful application of force in such a way that is intentionally injurious to the person or group against whom it applied. Injury is under stood to include psychological as well as physical harm. Police use arms to protect himself and the people.